Counseling And School Orientation Strategy of Educational Management in Rural Areas, Review - Angelica MUSAT; Constanta Laura ZUGRAVU; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2023)
Through the addressed topic, we try to point out some defining elements in the coordination of the class of students according to their needs, the topics they want to discuss, the things and information they want to find out or debate. Also through this topic we try to observe the vision of the leading teacher in his capacity as an advisor, coordinator, mediator who tries to help, understand and support his group of students.
Keywords: Motivation; Educational Management